Genome-wide analysis of the MADS-box gene family involved in salt and waterlogging tolerance in barley (Hordeum vulgare L.) - Wang, Feifei; Zhou, Zhenxiang; Zhu, Liang; Gu, Yangyang; Guo, Baojian; Lv, Chao; Zhu, Juan; Xu, Rugen (Frontiers in Plant Science, 2023)
MADS-box transcription factors are crucial members of regulatory networks underlying multiple developmental pathways and abiotic stress regulatory networks in plants. Studies on stress resistance-related functions of MADS-box genes are very limited in barley. To gain insight into this gene family and elucidate their roles in salt and waterlogging stress resistance, we performed genome-wide identification, characterization and expression analysis of MADS-box genes in barley. A whole-genome survey of barley revealed 83 MADS-box genes, which were categorized into type I (Mα, Mβ and Mγ) and type II (AP1, SEP1, AGL12, STK, AGL16, SVP and MIKC*) lineages based on phylogeny, protein motif structure. Twenty conserved motifs were determined and each HvMADS contained one to six motifs. We also found tandem repeat duplication was the driven force for HvMADS gene family expansion. Additionally, the co-expression regulatory network of 10 and 14 HvMADS genes was predicted in response to salt and waterlogging stress, and we proposed HvMADS11,13 and 35 as candidate genes for further exploration of the functions in abiotic stress. The extensive annotations and transcriptome profiling reported in this study ultimately provides the basis for MADS functional characterization in genetic engineering of barley and other gramineous crops.